Bronchitis 2011
DOI: 10.5772/18116
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Chronic Bronchitis in Chronic Obstructive Pulmonary Disease

Abstract: Hard cover, 190 pagesPublisher InTech

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 178 publications
(137 reference statements)
2
0
0
Order By: Relevance
“…Cigarette smoke causes an inflammatory reaction in bronchial or alveolar mucosa, and increased sensitivity to irritants. Previous studies have reported a higher prevalence of CB in smokers compared with nonsmokers (21)(22)(23)(24)(25)(26)(27)(28)(29). Our results also supported these findings and showed that in all regions, current smokers had a higher prevalence of self-reported CB compared with never smokers.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Cigarette smoke causes an inflammatory reaction in bronchial or alveolar mucosa, and increased sensitivity to irritants. Previous studies have reported a higher prevalence of CB in smokers compared with nonsmokers (21)(22)(23)(24)(25)(26)(27)(28)(29). Our results also supported these findings and showed that in all regions, current smokers had a higher prevalence of self-reported CB compared with never smokers.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, these prevalences varied according to location of residence. Numerous studies have demonstrated a relationship between socioeconomic status and CB (18,21,(29)(30)(31)(32)(33)(34). Educational attainment is among the key indicators of socioeconomic status and our results demonstrated that less than high school-educated participants were significantly more likely to self-report CB in the Ontario, Quebec, British Colombia and Atlantic regions.…”
Section: Discussionsupporting
confidence: 51%